CSR symbolic potential and business sustainability - Andre Ata Ujan (Cogent Business & Management, 2019)
This essay is an ethical reflection on the idea of corporate social responsibility (CSR) focusing on emphasizing its strategic position as the symbolic potential of business. As such, CSR is the reflection of business moral commitment to providing meaningful social activities, on the one hand, and, at the same time, intensifying ethical climate and ensuring long-lasting sustainability of the company. Three conditions are required to get realized such commitment: (i) the necessity of ensuring the quality of CSR programs; this can be satisfied by the Subject-Subject approach in the process of designing and performing CSR programs. (ii) Putting special concern on the long-lasting impacts of CSR programs on the community welfare. Blending community empowerment in every CSR programs would help realize better the concern. And, (iii) the necessity of the presence of ethical leadership in business. This would help institutionalize ethical values and hence preserve the sustainability of CSR as the symbolic potential of business. This will in turn help support further business sustainability.
Keywords: 650; symbolic potential; ethical climate; the subject-subject approach; communicative action; long-lasting impacts; ethical leadership